Analysis of mobilization and stakeholder participation: the case of Amhara Development Association - Seid, Ahmed Hussen; Ali, Adem Chanie (Ethiopian Journal of Language, Culture and Communication, 2024)
This article offers a comprehensive exploration of the complex dynamics involved in mobilization and stakeholder participation within the context of participatory development communication strategies. It specifically focuses on the Amhara Development Association and its practices in this regard. Employing an interpretative research paradigm, the study meticulously selects its sample using purpose-sampling techniques. Through a combination of in-depth interviews and thorough document analysis, a rich dataset is assembled to deeply investigate the strategies employed by the association. The findings of the study reveal a nuanced and multifaceted approach undertaken by the Amhara Development Association. This approach leverages various social institutions, media platforms, and governmental structures to mobilize communities toward self-realization through grassroots efforts. However, despite the association's concerted efforts, several challenges hinder the implementation of a fully participatory communication approach. One significant obstacle identified is the predominant role of the government, which sometimes limits the association's autonomy in decision-making and action. Furthermore, the association faces constraints in hiring an adequate number of communication experts, which affects its ability to fully embrace a participatory communication strategy. It suggests that the association should strive for greater independence by empowering its coordinators, project planners, and district-level structures. This empowerment aims to foster a more inclusive and participatory communication strategy, thus enhancing the association's effectiveness in community mobilization and ultimately contributing to sustainable development efforts in the region.